GENDER EQUALITY IN COSTA RICA: FROM RECOGNITION TO REDISTRIBUTION - Arias Ramírez, Rafael (2014)
For the purposes of this article, we address gender inequality as a dimension ofsocioeconomic inequality expressed in Costa Rica. Through the evaluation of a seriesof socioeconomic variables, we show that even when the country has moved forward interms of recognition of women rights, there is still much to do to achieve greater levels ofequality in the access to productive resources, socio-economic assets and employment.